The role of psychosocial factors affecting marital satisfaction in couples after marital infidelity - Douzadeh Emami, Mohammad Hasan; Nouri, Mohammad; Akhavan Mahdavi, Mahsa (Researcher Bulletin of Medical Sciences, 2019)
Background: Marital infidelity in our country is increasing and a few studies have been done on the factors influencing marital satisfaction afterwards. Therefore, in this study, we decided to determine the role of psychosocial factors affecting marital satisfaction in couples after marital infidelity. Method: This analytical-cross-sectional study was conducted on 235 couples who betrayed and did betrayal referred to relevant centers (counseling centers of Tehran and Mashhad’s university and court). Subjects completed marital satisfaction questionnaires (ENRICH)[1], attitudes toward infidelity scale (MARK WHATLY), adult attachment scale (RAAS), men’s and women’s sexual schema scale, and data were entered into SPSS 21 software after encoding and were analyzed by linear regression statistical method. Results: The results of data analysis showed that the most important factors affecting marital satisfaction were: attitude toward infidelity, scale of passionate – romantic scale, age and embarrassed - conservation schema (women) (p <0.05). Among these variables, age, attitude towards infidelity and embarrassed - conservation scale are inversely correlated with marital satisfaction, meaning that the higher the variance in terms of these variables, we will see less marital satisfaction after infidelity. But the passionate – romantic scale has a direct relationship with marital satisfaction, meaning that the more men are stronger in terms of this schema, the greater the marital satisfaction between the couples after the infidelity. Discussion and Conclusion: According to the findings of this research, it can be recommended to therapists to consider these variables in their therapeutic components to promote marital satisfaction after infidelity.